SARS-CoV-2 Psychiatric Sequelae: An Urgent Need of Prevention - Bottemanne, Hugo; Delaigue, Fanny; Lemogne, Cédric (Frontiers in Psychiatry, 2021)
Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), responsible of COVID-19 pandemic, is a worldwide-spread virus firstly described in December 2019 in Wuhan, China. Generally, viral infections are known to be a setting where individuals are at high risk of experiencing significant psychological and psychiatric complications. Infection-triggered disturbing of the immune system, and the stressful intensive unit care, could therefore be associated with psychopathology. Moreover, SARS-CoV-2 can potentially induce neuronal injuries, leading to neurocognitive disabilities. Previous studies report a high occurrence rate of psychopathological and neurocognitive conditions among COVID-19 survivors at one-month and three-month follow-up, highlighting the need of screening for these impairments in order to implement early interventions and secondary prevention. However, many psychiatric disorders can take several years to develop, and it is still difficult to differentiate between factors linked to the infection itself or to the global context of the pandemic. More studies are needed to investigate the effect of a range of factors including clinical, sociodemographic and inflammatory predictors. These efforts could be useful to identify high-risk individuals and inform targeted preventive actions.